Pentingnya Pelaku Industri Pariwisata Dibekali Uji Kompetensi Lewat Daring untuk Meningkatkan SDM Pariwisata di Indonesia - Nina Mistriani; Aletta Dewi Maria; Vera Damayanti (EDUTOURISM Journal Of Tourism Research, 2020)
The Importance of the Program The Government builds good habits to improve quality human resources that are applied in various sectors, including tourism. President Joko Widodo in his speech stated several factors that strengthen HR, namely healthy, smart, skilled and prosperous. The role of the tourism industry today is very important, because its role can provide recommendations to improve the capabilities and expertise in the field of tourism human resources. This study aims to analyze the importance of tourism industry players being guided online learning in competency tests, so that there is equity in improving Tourism Human Resources in Indonesia both in education and human resources working in the tourism industry. This is reinforced by BNSP allowing the implementation of remote competency assessment / testing carried out by LSP in accordance with Number: SE: 011 / BNSP / IV / 2020 dated April 3, 2020. This research uses a qualitative approach, which is an inductive approach. This type of descriptive research with case study research methods. The results showed that planning, organizing, developing, controlling the financing of competency tests require the carrying capacity of many stakeholders, so that the process can run smoothly. The success of increasing human resources is greatly influenced by the conditions of security and political stability, the carrying capacity of human resources who have expertise according to both quality and quantity, the budget used to develop facilities and infrastructure for tourism competency testing, legal policies that provide convenience, security, transparency and comfort for actors the tourism industry in the process of conducting online assessments in various regions in Indonesia.